Impact of coronavirus disease 2019 in dermatology - Jyoti Kumari; Surajit Gorai; Kinnor Das; Koushik Lahiri (Apollo Medicine)
Background: The whole of humankind was shaken by the coronavirus disease 2019 (COVID-19) pandemic. The field of dermatology has been affected by the pandemic as well. This short review aims to highlight the dents which the COVID-19 pandemic made in overall dermatology as a subject. Methodology: To find relevant material, searches were conducted on PubMed and Google Scholar. The evaluation took into consideration review articles, clinical trials, retrospective studies, observational studies, and case–control studies. Results: As a result of the COVID-19 pandemic, the number of cases in the dermatology outpatient department condensed, and dermatological procedures became scarce. Many cutaneous signs were witnessed in patients suffering from COVID-19. The health-care providers also suffered from cutaneous rash while using personal protective equipment during patient care. Various treatment guidelines were modified, including the use of various immunomodulators used in dermatology. The use of the vaccine against COVID-19 disease elicited various cutaneous side effects as well. In addition, the teaching and learning methods were also dented in this pandemic and were subjected to transformation. Conclusion: Dermatology as a subject was not untouched by the consequences of this pandemic. The disease pattern, the treatment guidelines, the consultation methods, and every other aspect of dermatology were subjected to change during this pandemic.